Profile of Students' Science Process Skills on Electrolyte and Non-Electrolyte Solution Material Assisted by E-LAPD Based on Guided Inquiry in Senior High School - Wahyu Setyoningrum, Retno; Hidayah, Rusly (Universitas Pahlawan Tuanku Tambusai, 2026)
This study addresses the low mastery of science process skills (SPS) of high school students on electrolyte and non-electrolyte solutions, which is exacerbated by the limitations of conventional E-LAPD in the Industry 4.0 era. It aims to identify the SPS profile of 25 grade XI students purposively sampled from a population of 75 people at Muhammadiyah 4 Sidayu High School, Gresik, through a mixed descriptive approach to the preliminary study design. The instrument includes six reliable SPS test essay questions (Cronbach's Alpha 0.80) measuring observation, classification, prediction, measurement, communication, and conclusion drawing, plus questionnaires and interviews, analyzed using SPSS 26 descriptive statistics, Azwar categorization, and qualitative content analysis. The results show that 60% of students have very low SPS and 40% have low without medium or high achievement, with the percentage of observation indicators (17.13%), classification (16.82%), prediction (16.21%), measurement (17.13%), communication (13.91%), and conclusion drawing (18.81%). In conclusion, conventional E-LAPD fails to facilitate inquiry, so it is necessary to develop guided inquiry-based learning for systematic KPS improvement.